2014
DOI: 10.1177/1352458514525871
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence and no latitude gradient of multiple sclerosis in Norway

Abstract: The prevalence of multiple sclerosis (MS) is increasing, and the presence of a latitude gradient for MS risk is still discussed. We present the first nationwide prevalence estimates for Norway, spanning the latitudes from 58-71 degrees North, in order to identify a possible latitude gradient. Information from the Oslo MS Registry and the Norwegian MS Registry and Biobank was combined with data from the Norwegian Patient Registry, the Norwegian Prescription Database and Statistics Norway. We estimated a crude p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 10 publications
4
50
2
1
Order By: Relevance
“…The prevalence rate of 211/100 000 inhabitants was higher than a recent prevalence report of 186/100 000 in Western Norway. 9 These diverging results are most likely a result of the limitation of using data from the National Patients Registry included in this recent nationwide study. 9 Previous Norwegian studies using hospital records (as in our study) have reported MS prevalence rates of 170/100 000 in the south-eastern county of Oslo, 10 180/100 000 in the southern county of Vest-Agder 7 and 185.6/100 000 in the eastern county of Oppland.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The prevalence rate of 211/100 000 inhabitants was higher than a recent prevalence report of 186/100 000 in Western Norway. 9 These diverging results are most likely a result of the limitation of using data from the National Patients Registry included in this recent nationwide study. 9 Previous Norwegian studies using hospital records (as in our study) have reported MS prevalence rates of 170/100 000 in the south-eastern county of Oslo, 10 180/100 000 in the southern county of Vest-Agder 7 and 185.6/100 000 in the eastern county of Oppland.…”
Section: Discussionmentioning
confidence: 76%
“…9 These diverging results are most likely a result of the limitation of using data from the National Patients Registry included in this recent nationwide study. 9 Previous Norwegian studies using hospital records (as in our study) have reported MS prevalence rates of 170/100 000 in the south-eastern county of Oslo, 10 180/100 000 in the southern county of Vest-Agder 7 and 185.6/100 000 in the eastern county of Oppland. 8 The prevalence rate in Hordaland was, thus, similar to the latest report from the UK, 11 sample collection termination day, in order to calculate the valid prevalence.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The authors also intend to provide an update on the MS prevalence in Norway, compared to the first nationwide prevalence study published in 2014 2. Grytten et al estimate a nationwide prevalence of MS in Norway of 208 per 100,000 on 31 December 2013, which is not far from our reported 203 per 100,000 on 1 January 2012 (although confidence intervals were not given for the newly estimated 2013 data in the review article).…”
Section: A Step Back For Ms Prevalence Studies In Norwaymentioning
confidence: 91%
“…Forekomsten av multippel sklerose er økende, og det er beregnet at om lag 10 000 mennesker i Norge har sykdommen (1). Multippel sklerose reduserer livslengden med 5 -10 år og er en hyppig årsak til nevrologisk invaliditet.…”
unclassified